Modular Multilevel Converters Part-I: A Review on Topologies, Modulation, Modeling and Control Schemes - Sreedhar Madichetty; Abhijit Dasgupta (Institute of Advanced Engineering and Science, 2014)
This article is devoted to the Multi-level inverters review and in particular to the form and function of modular multilevel inverters (MMI), with their different topologies, modulation, modeling and control schemes Detailed analysis with their functions of MMI has been made in comprehensive manner with existing literature available till date. All existing methods are compared in detail with proposal for the best methods available. The article has made strategic conclusions on MMI to make the system more robust in operation with less complexity in design and control.DOI: http://dx.doi.org/10.11591/ijpeds.v4i1.5020